Developing Teacher Competencies for Teaching Evolution across the Primary School Curriculum: A Design Study of a Pre-Service Teacher Education Module - Susan Hanisch; Dustin Eirdosh (MDPI AG, 2023)
Numerous studies indicate that evolutionary concepts can and should be taught at the primary school level. However, teaching evolution in primary school is presumably not yet the norm globally. At the same time, the educational potential of evolutionary concepts lies in their applicability to many curriculum topics in the natural and social sciences. Capitalizing on this potential requires broad teacher content knowledge (CK) and pedagogical content knowledge (PCK) about the teaching of evolutionary concepts. However, not much is known regarding ways to develop primary teacher CK and PCK during pre-service training. In this article, we present the iterative design, implementation, and mixed methods formative evaluation (based on a design-based research framework) of a pre-service teacher education module. Its aim was to promote the development of pre-service primary school teacher CK, PCK, as well as motivation and confidence for teaching evolution across the primary school curriculum. Results indicate that pre-service teachers can be supported and motivated to teach evolutionary concepts across various themes in the primary school curriculum through a semester long course. Participants were able to develop core aspects of CK and PCK regarding the teaching of evolutionary concepts in primary school. The resulting module design integrates existing collective PCK on teaching evolution at the primary level as well as novel design considerations and teaching approaches that can be integrated into pre-service teacher education programs. However, challenges remain, particularly regarding the integration of evolutionary concepts in mandated curriculum standards such that the educational potential of evolution can be fully capitalized on by teachers.